Ответ(ы) на вопрос:
1 вариант решения:
[latex](3 \sqrt{5}- \sqrt{20} )\cdot \sqrt{5} =3 \sqrt{5}\cdot \sqrt{5} - \sqrt{20}\cdot \sqrt{5} =3 \sqrt{5\cdot 5} - \sqrt{20\cdot 5} =\\ =3 \sqrt{5^2} - \sqrt{100} =3\cdot5- \sqrt{10^2} =15-10=5\\[/latex]
2 вариант решения:
[latex](3 \sqrt{5}- \sqrt{20} )\cdot \sqrt{5} =(3 \sqrt{5}- \sqrt{4\cdot5} )\cdot \sqrt{5} =(3 \sqrt{5}- \sqrt{2^2\cdot5} )\cdot \sqrt{5} =\\ =(3 \sqrt{5}- 2\sqrt{5} )\cdot \sqrt{5} = \sqrt{5}\cdot \sqrt{5}= \sqrt{5\cdot5}= \sqrt{5^2}=5 [/latex]
Не нашли ответ?
Похожие вопросы